Geotechnical and Rock Mass Characterization Using Seismic Refraction Method at Kajang Rock Quarry, Semenyih, Selangor Darul Ehsan - Kausarian, Husnul; Shamsudin, Abd. Rahim; Yuskar, Yuniarti (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Rock mass characterization study at the Kajang Rock quarry wasper formed with the use of refraction seismic method. Rock Quality Designation (RQD) can be measured in the field. Discontinuity survey and processing of seismic data determined from 4 locations have been examined in this site. Based on refraction seismic method, velocity of P waves (Vp) can be obtained, and the weathering grade of rock mass has been determined. Location 1 consist of 5 weathering zone with the range of Vp of 200-5400 m/s. Location 2 consist of 4 weathering zone with the Vp range of 600-5600 m/s. Location 3 consist of 4 weathering zone with range of Vp of 800-5250 m/s. Location 4consist of 5 weathering grade with the range of Vp of 250-5000m/s. Rock Quality Designation (RQD) Location 1 shows the rock is excellent (98.63%), in Location 2, RQD shows the rock is good(98.38%), in Location 3 RQD shows the rock is excellent (99.03%), in Location 4 RQD shows the rock is excellent (96.43%).